Afghanistan's Geopolitical and Geo-economic Significance in Regional Connectivity and Development - YAR, Fayaz Gul Mazloum; ZAHID, Shamsurahman; MIAKHIL, Jan Mohammad (Indonesia Strategic Sustainability, 2023)
Purpose - The emergence of industrial hubs focused on oil and gas energy has fortified economic structures by integrating production, transit, and energy consumption, a phenomenon known as